From pain to tumor immunity: influence of peripheral sensory neurons in cancer - Mardelle, Ugo; Bretaud, Ninon; Daher, Clara; Feuillet, Vincent (Frontiers in Immunology, 2024)
The nervous and immune systems are the primary sensory interfaces of the body, allowing it to recognize, process, and respond to various stimuli from both the external and internal environment. These systems work in concert through various mechanisms of neuro-immune crosstalk to detect threats, provide defense against pathogens, and maintain or restore homeostasis, but can also contribute to the development of diseases. Among peripheral sensory neurons (PSNs), nociceptive PSNs are of particular interest. They possess a remarkable capability to detect noxious stimuli in the periphery and transmit this information to the brain, resulting in the perception of pain and the activation of adaptive responses. Pain is an early symptom of cancer, often leading to its diagnosis, but it is also a major source of distress for patients as the disease progresses. In this review, we aim to provide an overview of the mechanisms within tumors that are likely to induce cancer pain, exploring a range of factors from etiological elements to cellular and molecular mediators. In addition to transmitting sensory information to the central nervous system, PSNs are also capable, when activated, to produce and release neuropeptides (e.g., CGRP, SP) from their peripheral terminals. These neuropeptides have been shown to modulate immunity in cases of inflammation, infection and cancer. PSNs, often found within solid tumors, are likely to play a significant role in the tumor microenvironment, potentially influencing both tumor growth and anti-tumor immune responses. In this review, we discuss the current state of knowledge about the degree of sensory innervation in tumors. We also seek to understand whether and how PSNs may influence the tumor growth and associated anti-tumor immunity in different mouse models of cancer. Finally, we discuss the extent to which the tumor is able to influence the development and functions of the PSNs that innervate it.